A relação entre cultura, clima e engajamento dos colaboradores de uma cooperativa situada no Estado do Rio Grande do Sul - Reolon, Eloísa Feistler (2022)
This research, which was applied in a credit cooperative in the state of Rio Grande do Sul, is a quantitative research with a descriptive purpose, with the objective of analyzing the relationship between commitment, entrenchment and the organizational climate with the organizational engagement of the employees of the cooperative. For data collection, a questionnaire with closed questions was used to investigate the levels of organizational commitment, work engagement, its relationship with the organizational climate and the levels of organizational entrenchment. It was noted that, for a long time, the committed employee was the one who stayed for a long time in the organization, or did not disconnect from his work, but in current times, this is no longer enough, so much so that occupational diseases, arising from their activities/attitudes have been pointed out in studies due to these facts. It is noted that this is no longer sufficient to determine organizational commitment and the level of engagement in the work environment. What really determines is the fact that employees are in the organization because they really want to and not because they need to. The survey was carried out with 52 employees of the cooperative. With the results of this research, it was possible to verify that the employees have a high level of organizational commitment and organizational engagement, mainly, a dedication in their activities, but those employees who have a certain level of entrenchment no longer have a high organizational engagement. In this way, it was possible to draw up an action plan to encourage improvements in these dimensions and strengthen the organizational climate of the cooperative.